BERKATEKESE MEMBANGUN JEMAAT DENGAN ORIENTASI KERAJAAN ALLAH - Fransiskus Heryman Surya Gadur (STIKAS Santo Yohanes Salib Kalimantan Barat, 2019)
The relevant Catechism in the midst of the struggling of the life of the faithful is an urgent task of the Church. Catechism cannot be given just to the point of the church’s routine, but should be started from the basic needs of the faithful and the church itself as to grow in faith. Model of catechism that oriented to the kingdom of God is one of the answers toward the struggling of the faithful in relation to the environment and local situation as well as with God. There is a positive hope to create such group of the faithful through this effort. St. Therese of the Child Jesus’s Parish, Simpang Tiga chose such model to discover the reality of catechism’s activity during these periods. By such perspective of catechism, this Parish wants to shape a strong and substantial communion of faithful – having an experience of God, and dialogue with their roots of life in Kalimantan.